The Role of Hydrogen Sulfide and H2S-donors in Myocardial Protection Against Ischemia/Reperfusion Injury - Citi, Valentina; Piragine, Eugenia; Testai, Lara; Breschi, Maria C.; Calderone, Vincenzo; Martelli, Alma (Current Medicinal Chemistry, 2018)
Hydrogen sulfide (H2S), previously known only as a toxic agent, in the last decades has been recognized as an important endogenous gasotransmitter, playing a key role in the homeostasis of the cardiovascular system. In the last years, the growing evidence about a protective role exhibited by H2S against myocardial ischemia/reperfusion (I/R), led to an increasing interest for the possible mechanism of action accounting for the H2S cardioprotective effect, and to the discovery of the involvement of several targets. Currently, many mechanisms of action have been proposed and verified through in vitro and in vivo models of I/R injury, such as the anti-inflammatory or the anti-oxidant ones, or mechanisms of Ssufhydration able to modify proteins such as ion channels. Particular attention was focused on the mitochondrial preservation and on anti-apoptotic mechanisms, and finally even a pro-angiogenesis effect has been described. At the same time, the design, the development and the pharmacological characterization of moieties able to release H2S, employed alone as H2S-donor, or conjugated with another drug in hybrid molecules, led to the production of novel chemical entities in the panorama of cardioprotective drugs.
Keywords: hydrogen sulfide